Acute IOP elevation with scleral suction: effects on retrobulbar haemodynamics. Issue 12 (December 1996) - Harris, A; Joos, K; Kay, M; Evans, D; Shetty, R; Sponsel, W E; Martin, B
Abstract : AIMS/BACKGROUND: Mechanical and vascular factors may both contribute to glaucoma. This study investigated the relation of mechanical to vascular factors by examining how acute IOP elevation altered flow velocities in the central retinal and ophthalmic arteries. METHODS: IOP was elevated from a baseline near 14 to approximately 45 mm Hg using suction ophthalmodynamometry. During recovery from scleral suction, IOP fell to near 8 mm Hg. At each IOP, peak systolic and end diastolic velocities (PSV and EDV) were measured in the central retinal and ophthalmic arteries using colour Doppler imaging (Siemens Quantum 2000). Eleven healthy people served as subjects. RESULTS: Acute elevation in IOP had no effect upon PSV, EDV, or the derived resistance index in the ophthalmic artery: flow velocities in this vessel were identical at IOP of 8 mm Hg or 45 mm Hg. In contrast, in the central retinal artery, PSV and EDV fell, and the resistance index rose, in steady progression as IOP was acutely elevated (each p < 0.01). At IOP of 45 mm Hg, EDV was virtually absent and the resistance index was very nearly 1.0. CONCLUSION: Ophthalmic arterial haemodynamics are unrelated to acute fluctuations of the IOP over a wide range, suggesting that ocular hypertension itself cannot induce vascular dysfunction in this artery. In contrast, flow velocities in the central retinal artery were highly IOP dependent, implying that haemodynamic and mechanical factors are closely linked in this vascular bed.